Persepsi Mempengaruhi Rendahnya Pemakaian Kontrasepsi Implan - Akhmad, Reznita Adityani D; Saadong, Djuhadiah; Afriani, Afriani; Hidayati, Hidayati (Jurnal Kebidanan Malakbi, 2022)
Indonesia, there are relatively few users of contraceptive implant methods compared to other types of contraception, although implants have a higher level of effectiveness than other contraceptives. The government has made various efforts but to no avail. The purpose of the study was to determine the factors that influence the low use of contraceptive implants at the Minasa Upa Health Center in Makassar City. The research method is an analytic survey with a "cross-sectional study" method and sampling using a simple random sampling technique of 67 people. The study was conducted in MarchMay 2021 using a questionnaire. Statistical analysis was performed using the Chisquare test = 0.05. The results showed that the phi value of perceived significance was p=0.001(p>0.05), socioeconomic p=0.756 (p>0.05), and the anxiety factor was p=0.369 (p>0.05). So it is known that perception has a significant relationship with the low use of contraceptive implants methods, while socioeconomic and anxiety factors do not have a significant relation. Therefore, it is recommended for health workers to conduct regular counseling about contraception, especially contraceptive implant methods, to increase mothers' knowledge so that negative perceptions of contraceptive implant methods can be reduced.